Rural Public Libraries and Digital Inclusion: Issues and Challenges. - Real, Brian; Bertot, John Carlo; Jaeger, Paul T. (Information Technology & Libraries, 2014)
Rural public libraries have been relatively understudied when compared to public libraries as a whole. Data are available to show that rural libraries lag behind their urban and suburban counterparts in technology service offerings, but the full meaning and effect of such disparities is unclear. The authors combine data from the Public Library Technology and Access Study with data from smaller studies to provide greater insight to these issues. By filtering these data through the digital inclusion framework, it becomes clear that disparities between rural and nonrural libraries are not merely a problem of weaker technological infrastructure. Instead, rural libraries cannot reach their full customer service potential because of lower staffing (but not lower staff dedication) and funding mechanisms that rely primarily on local monies. The authors suggest possible solutions to these disparities while also discussing the barriers that must be overcome before such solutions can be implemented.